Media Film Sebagai Alternatif Pembelajaran Bahasa Inggris - Ibnu Ahmad Al-Ghazali; Mochammad Riski Pebriansah; Fajar Bumi Maulana; Sri Mulyeni (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2026)
This study explores the use of English movies as an alternative approach to English language learning for university students, examining its impact on language skills, learning motivation, and cultural awareness. A qualitative narrative inquiry method was employed to capture students' experiences and perspectives on learning through films. The research involved eight university students, selected purposefully, and data was gathered through in-depth interviews. The findings suggest that watching English movies significantly improves students' listening and speaking skills, vocabulary, fluency, and real-world language usage. English subtitles were found to play a critical role in enhancing students' understanding of sentence structures, spelling, and contextual meanings. Additionally, films were perceived as an engaging learning tool that reduced monotony and boosted motivation compared to traditional methods reliant on textbooks and grammar exercises. Moreover, students reported an increased understanding of cultural nuances, as films exposed them to authentic communication styles, expressions, and social contexts. However, the effectiveness of film-based learning depends on its consistent integration, the careful selection of films that match students' language proficiency levels, and structured pedagogical support. This study concludes that films, when systematically implemented, offer a dynamic and relevant method to engage students and enhance their language learning experience, making it a promising educational tool in higher education.